INHBA gene silencing inhibits proliferation, migration, and invasion of osteosarcoma cells by repressing TGF-β signaling pathway activation - Hongyu Zhang; Yuemei Huang; Qiuting Wen; Yan Li; Lin Guo; Na Ge (Journal of Orthopaedic Surgery and Research)
Abstract Background Osteosarcoma (OS) is a refractory malignancy. This study aimed to explore the roles and mechanisms of Inhibin subunit beta A (INHBA) in OS. Methods INHBA expression levels in OS tissues and cells were assessed using RT-qPCR and western blotting. The impact of INHBA silencing on OS development was then explored by transfecting the OS cell lines U2OS and MG63 with INHBA-small interfering RNA (siRNA). The influence of INHBA silencing on U2OS and MG63 cell proliferation, migration, and invasion was examined using MTT and Transwell assays. Epithelial–mesenchymal transition (EMT) markers (E-cadherin and N-cadherin) were analyzed by RT-qPCR. The expression of genes involved in cell proliferation, migration, invasion, and the TGF-β signaling pathway was evaluated by western blotting and RT-qPCR. Results INHBA levels were elevated in the OS tissues and cells. Furthermore, the transforming growth factor-β (TGF-β) signaling pathway of OS cells was suppressed in response to INHBA-siRNA, whereas proliferation, migration, and invasion of OS cells were inhibited. Besides, INHBA-siRNA significantly inhibited OS cell EMT, evidenced by enhanced E-cadherin mRNA expression and reduced N-cadherin mRNA expression. Further mechanistic studies revealed that the TGF-β1 agonist SRI-011381 hydrochloride increased OS cell proliferation, migration, and invasion after INHBA downregulation. Conclusion We found that INHBA silencing could play a vital role in OS via TGF-β1-regulated proliferation, migration, and invasion.